Species Composition of Termites (Isoptera) in Different Cerrado Vegetation Physiognomies - Danilo Elias Oliveira; Tiago Fernandes Carrijo; Divino Brandão (Sociobiology)
Little is known about the termite fauna of the different vegetation physiognomies in the Cerrado biome. It is suggested that the species compositions in grassland and savanna areas are closely related to each other, and quite distinct from those of forests. This study compared the species composition from five different physiognomies of Cerrado, and tested the hypothesis that the termite faunas of savannas and grasslands form a distinct group from that of forests. The study was conducted in the Parque Estadual da Serra de Jaraguá, state of Goiás, Brazil. Termites were sampled from two physiognomies of savanna, one natural grassland, one pasture, and one gallery forest. A transect with 10 parcels of 5x2 m was established in each physiognomy. The relative abundance was inferred by the number of encounters, termites were classified in feeding guilds, and the dissimilarity in the species composition between the physiognomies was calculated. A total of 219 encounters, of 42 species of two families were recorded. The most abundant feeding guilds were the humivores (98) and xylophages (55). The physiognomies with the largest number of species were rupestrian cerrado (23 species) and cerrado sensu stricto (21). The physiognomies had a similar species composition (less than 55% dissimilarity), mainly the natural open areas. The hypothesis of a distinct fauna of termites in forest vegetation was refuted. The termite fauna of gallery forest is very different from that of pasture, but most species also occur in natural open areas. The impact of pasture on the diversity and composition of termites seems to be significant, but the impact is even greater on the proportion of the feeding guilds, reducing the proportion of xylophages and intermediates.